PORTFOLIOS: WILL THEY ENDURE? - Ediger, Marlow (College Student Journal, 2000)
Portfolio methods of appraising pupil progress are learner centered. However, the final portfolio to be evaluated is time consuming and should be assessed by more than one person to notice interrater/interscorer reliability. This also represents an item of expense, unless teachers are willing to do this voluntarily within an already busy schedule. Testing to notice pupil achievement is also costly; however, the results can be obtained quickly involving large number of pupils with the use of machine scoring and printouts of achievement. Here, numerical results are available for each pupil and they are relatively easy to interpret. Portfolio results are labeled as being subjective as compared to the label of objectivity being given to test results.